Residência Multiprofissional em Saúde Coletiva: percepções sobre o papel do profissional de educação física junto à estratégia de saúde da família - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This study aims to investigate professionals working in Family Health Strategy perceptions of the role of Professional of Physical Education in Primary Care. It is a qualitative study with exploratory aims and characterized as case study. The analytical corpus consists of 06 semi- structured interviews with Health Professionals who work in a Family Health Strategic and are part of the Multi-professional team of a Public Health Residency Program. Data processing was based on content analysis. The perceptions of the Health Professionals are in the sense of attributing relevance to the role played by the Physical Education Professional in Primary Care. It indicates that health units do not offer structural conditions to the Professional of Physical Education activities development. It indicates varied degrees of comprehension of Professional of Physical Education skills and competences, which limits the perception of its role. Representation of Professional of Physical Education insertion in Primary Care emphasizes since the improvement of users health until the aid in the results achieved by unit health team, as well as improvement of the community welfare conditions.
Multiprofessional Residency in Collective Health: perceptions about the role of the professional of physical education in family Health Strategy
Keywords: Promotion Health; Primary Care; Physical Education; Public Health; Physical Activity; Educação Física; Atenção Primária; Saúde Coletiva; Promoção da Saúde; Atividade Física; CNPQ::CIENCIAS DA SAUDE